Population Dynamics Of Calamus Castaneus Griff. In Selected Forest Reserve In Northern Region Of Peninsular Malaysia - Rusdi, Nur Diana Mohd (2019)
The population dynamics of rattan in Malaysian forests was not fully documented. Hence, the major aim of this study was to investigate the population dynamics pattern of Calamus castaneus; a non-climbing rattan. This study was conducted in selected forest reserve in the northern region of Peninsular Malaysia namely Segari Melintang Forest Reserve in Perak, Teluk Bahang Forest Reserve and Bukit Mertajam Forest Eco Park in Pulau Pinang from March 2017 until March 2018. The objectives of this study were; 1) to evaluate the regeneration status and growth of C. castaneus. 2) to investigate flowering and fruiting duration, and 3) to correlate the microclimate parameters and soil properties on the population dynamics of C. castaneus. In each study site, five plots with the size of 10 m x 10 m (100 m²) each were established. All C. castaneus individuals inside the plot were marked with numbered plastic tags. A total of 180 individuals was evaluated in all study sites; Teluk Bahang FR (52 individuals), Segari Melintang FR (86 individuals) and Bukit Mertajam FEP (42 individuals). Present analysis showed that the regeneration status, growth, duration of flowering and fruiting, as well as different environmental would influence the population dynamics pattern of C. castaneus. The findings of this study revealed that the regeneration rate of C. castaneus had no significant difference (p < 0.05) using Kruskal-Wallis test between each site which means the regeneration status is all study locations is nearly the same.